Radiation exposure in 90Y-Zevalin therapy - Geworski, L.; Zöphel, K.; Rimpler, A.; Barth, I.; Lassmann, M.; Sandrock, D.; Zander, A.; Halm, T.; Hänscheid, H.; Hofmann, M.; Reiners, Chr.; Munz, D. L. (Nuklearmedizin - NuclearMedicine, 2006)
Aim of this study was the assessment of the radiation exposure from preparation and application of 90Y-Zevalin, the measurement of the dose rate at the patient, the exposure of family members as well as the determination of the activity concentration in urine of patients. Methods: Overall data from 31 therapeutic administrations carried out in four institutions were evaluated. During preparation and application of 90Y-Zevalin the finger exposures of radiochemists, technicians, and physicians were measured. The dose rate of the patient was measured immediately after radioimmunotherapy. In patients treated in a nuclear medicine therapy unit, urine was collected over a two day period and the corresponding activity was determined. Family members of outpatients were asked to wear a dosimeter over a seven day period. Results: During the preparation we found a maximum skin dose of 6 mSv at the average, and during application of 3 mSv, respectively. After administration of 90Y the dose rate was 0.4±0.1 μSv/h at 2 m distance. Urine measurements yielded a cumulated 24 h excretion of 3.9±1.4% and 4.4±1.4% within 48 h, respectively, that is equivalent to 43±18 and 50±20 MBq of 90Y, respectively. Family members received a radiation exposure of 40±14 μSv over seven days. Conclusion: During preparation and application of 90Y-Zevalin appropriate radiation shielding is necessary. For family members as well as nursing staff no additional special radiation protection measures beyond those being common for other nuclear medicine procedures are necessary.
Keywords: Ibritumomab tiuxetan; Zevalin; 90Y; β--rays; Bremsstrahlung; radioimmunotherapy; radiation exposure; skin dose; radiation protection